The effect of atorvastatin on macular pigment optical density: experimental study - Su Su, Aye Chan; Kunching, Sumate (Journal of Health Science and Alternative Medicine, 2021)
Introduction: Low-density lipoprotein (LDL)- and high-density lipoprotein (HDL) cholesterol are serum lipoproteins involved in the transportation of lutein and zeaxanthin to the retina to serve as macular pigments (MPs). Atorvastatin, a serum cholesterol-lowering agent, can affect the MP distribution and reduce macular pigment optical density (MPOD). MPOD is one of the best indicators of retinal diseases such as age-related macular degeneration. Objective: To study the effect of atorvastatin on the level of MPOD in people taking atorvastatin 10 mg for more than 6 months. Methodology: An experimental study was conducted on 44 Asian men and women, aged between 30 and 60 years and residing in Thailand, who were recruited and divided into two equal groups. The first group was currently taking atorvastatin 10 mg for at least 6 months, whereas the control group did not receive atorvastatin. MPOD was measured in all participants using the macular pigment screener-II. Participants were required to sign an informed consent form and complete questionnaires regarding various factors that may influence the MPOD. Data were analyzed using the Kolmogorov–Smirnov test and t-test to compare the MPOD between groups. Results: The mean MPOD of the experiment group was 0.3295 ± 0.1311 DU, whereas that of the control group was 0.4686 ± 0.1491 DU. The mean MPOD of the experimental group was significantly lower than that of the control group (p-value = 0.002). Conclusion: Patients taking atorvastatin had a lower MPOD than those who did not.